Abrupt decline in oxycodone-caused mortality after implementation of Florida's Prescription Drug Monitoring Program. (1st May 2015) - Delcher, Chris; Wagenaar, Alexander C.; Goldberger, Bruce A.; Cook, Robert L.; Maldonado-Molina, Mildred M.
Highlights: A 25% drop in oxycodone-caused deaths occurred after the start of the Prescription Drug Monitoring Program (PDMP) in Florida. Our findings suggest that health care provider use of the PDMP played a role. Results have implications for national prescription drug abuse policy. Abstract: Background: In Florida, oxycodone-caused deaths declined substantially in 2012. Multiple important law enforcement, pharmaceutical, policy, and public health actions occurred concurrently, including implementation of a statewide Prescription Drug Monitoring Program (PDMP). The effects of the PDMP on oxycodone-caused mortality in Florida were evaluated. Methods: A time-series, quasi-experimental research design with autoregressive integrated moving average (ARIMA) statistical models, including internal and external covariates. Data included 120 repeated monthly observations. Monthly counts of oxycodone-caused deaths, obtained from the Florida Medical Examiners Commission (MEC) was the outcome variable. Models included market-entry of tamper-resistant oxycodone HC1 controlled release tablets (OxyContin ® ), enforcement crackdowns (Operation Pill Nation), and regulation by FL House Bill 7095, measured by the monthly count of Florida pain management clinics closed. Two approaches were used to test the PDMP's hypothesized effect: (1) a binary indicator variable (0 = pre-implementation, 1 = post-implementation), and (2) a continuous indicator consisting of the number of PDMP queries by health care providers. Results: Oxycodone-caused mortality abruptly declined 25% the month after implementation of Florida's PDMP ( p  = 0.008). The effect remained after integrating other related historical events into the model. Results indicate that for a system-wide increase of one PDMP query per health care provider, oxycodone-caused deaths declined by 0.229 persons per month ( p  = 0.002). Conclusions: This is the first study to demonstrate that the PDMP had a significant effect in reducing oxycodone-caused mortality in Florida. Results have implications for national efforts to address the prescription drug epidemic.